Extremely Robust and Multifunctional Nanocomposite Fibers for Strain‐Unperturbed Textile Electronics. Issue 15 (4th March 2023) - Gu, Jianfeng; Li, Fengchao; Zhu, Yinbo; Li, Donghui; Liu, Xue; Wu, Bao; Wu, Heng‐An; Fan, Xiangqian; Ji, Xinyi; Chen, Yongsheng; Liang, Jiajie
Abstract: Textile electronics are needed that can achieve strain‐unaltered performance when they undergo irregular and repeated strain deformation. Such strain‐unaltered textile electronics require advanced fibers that simultaneously have high functionalities and extreme robustness as fabric materials. Current synthetic nanocomposite fibers based on inorganic matrix have remarkable functionalities but often suffer from low robustness and poor tolerance against crack formation. Here, we present a design for a high‐performance multifunctional nanocomposite fiber that is mechanically and electrically robust, which was realized by crosslinking titanium carbide (MXene) nanosheets with a slide‐ring polyrotaxane to form an internal mechanically‐interlocked network. This inorganic matrix nanocomposite fiber featured distinct strain‐hardening mechanical behavior and exceptional load‐bearing capability (toughness approaching 60 MJ m −3 and ductility over 27%). It retained 100% of its ductility after cyclic strain loading. Moreover, the high electrical conductivity (>1.1 × 10 5 S m −1 ) and electrochemical performance (>360 F cm −3 ) of the nanocomposite fiber can be well retained after subjecting the fiber to extensive (>25% strain) and long‐term repeated (10 000 cycles) dimensional changes. Such superior robustness allowed for the fabrication of the nanocomposite fibers into various robust wearable devices, such as textile‐based electromechanical sensors with strain‐unalterable sensing performance and fiber‐shaped supercapacitors with invariant electrochemical performance for 10 000 strain loading cycles. Abstract : An extremely robust and multifunctional nanocomposite fiber is fabricated by introducing a mechanically interlocked network inside the fibrous structure. The fiber obtains strong resistance against structural crack formation and propagation, and the fiber‐based textile electronics show exceptional robustness. The textile‐based electromechanical sensors exhibited strain‐unalterable sensing performance and fiber‐shaped supercapacitors showed invariant electrochemical performance during large and cyclic strain perturbations.